A comparative study of the emission of volatile organic compounds (VOCs) from different sulfur content crude oils. (18th July 2018) - Salih, Yousif Mustafa; Karim, Abdulsalam Rahim; Khurshid, Ibrahim
ABSTRACT: A new lab-made passive sampler method was employed to collect volatile organic compounds (VOCs) and volatile sulfur compounds (VSCs) which they were emitted from the spill of two different sulfur content crude oils. In this study, two different models have been used to represent of spill crude oil in two different areas, a laboratory and field model for spill crude oil on the surface area and pipeline leak respectively. The effective meteorological parameters such as rain, wind speed, and air temperature were controlled. The results show that the emitted VOCs were inversely proportional to the sulfur content crude oils.